ANALYSIS OF DIGITAL LITERACY COMPETENCIES OF ECONOMICS TEACHERS IN ONLINE LEARNING DURING THE COVID 19 PANDEMIC (JURNAL ECONOMICA : Research of Economic And Economic Education, 2021)
This study aims to describe the digital literacy of economics teachers in online learning as an effect of the COVID-19 pandemic. The approach used in this research is descriptive quantitative approach with explanatory survey method. Simple random sampling techniques was used for collecting the data. From the total population of 135 economics teachers, the researcher took a sample of 56 economics teachers, where this sample was taken from 28 public schools consisting senior high schools and Islamic high school in Tasikmalaya Regency. Respondents were given statements totaling 26 items with two choices, namely Yes and No, then the collected data was given a score based on the Guttman scale. The questionnaires that have been distributed are tabulated for easy calculation. After the data was tabulated, the results were described according to the conditions in the field. The results of this study indicate that the digital literacy of economics teachers in online learning during the Covid 19 pandemic is relatively high, namely 55.30%, however, if viewed from the four aspects of digital literacy skills for the guidance aspect of hypertext, it is still low. Therefore, evaluation is still needed to improve teachers’ understanding of hypertext, so that teachers will be more effective in accessing existing information to prepare for online learning.